Human resource strategies for organizational ambidexterity. Issue 4 (3rd June 2019) - Kim, Andrea
Abstract : Purpose: The purpose of this paper is to propose a comprehensive framework that delineates how human resource (HR) practices are differentially configured for exploitative and explorative innovation as well as how the sets of HR practices support these two types of innovation. Design/methodology/approach: Based on the structural ambidexterity approach and a bottom-up process in the multilevel theories, this research derives the need for the differential managerial structures for exploitation and exploration at the unit level. In addition, the Input–Process–Outcome model of team effectiveness and multilevel theories are employed to discuss the internal nature (e.g. resources, work styles) of exploiting and exploring units. Finally, building on strategic HR management literature, this research configures exploitation-targeted and exploration-targeted HR systems and delves into how these differentiated HR systems generate differential inputs of human capital resources and thereby foster exploitative and explorative innovation processes. Findings: This research proposes several factors for exploitation and exploration, including: necessary inputs (i.e. commitment, narrowness, and cohesion for exploitation vs thoughtfulness, breadth, and openness for exploration), idiosyncratic innovation processes (i.e. convergent collective cognition vs divergent collective cognition), and differentiated HR systems comprised of different forms of unit staffing (homogeneity vs heterogeneity), performance appraisal, incentives, and training and development (short-term vs long-term orientation). Originality/value: The proposed theoretical framework contributes to an improved understanding of the psychological foundation of organizational ambidexterity and systematizing how diverse HR practices work together to elicit exploitative and explorative innovation from employees.